"How are you vulnerable?": Using participation for vulnerability analysis in emergency planning. Issue 9 (2nd September 2017) - Rossignol, Nicolas; Turcanu, Catrinel; Fallon, Catherine; Zwetkoff, Catherine
Abstract : Scientists in many fields of research have developed models, theories, and concepts attempting to grasp and manage dangers that are often difficult to imagine. Among the different perspectives, the science and technology studies (STS) vulnerability approach seems very promising. Relying on a constructivist paradigm, it is based on an inductive collection and analysis of a wide range of factors, with a particular focus on cultural factors and actual day-to-day practices. In this paper, we present the roots of this approach and we display findings based on three case studies exploring emergency planning in three different contexts (a city near a SEVESO plant, a school near a nuclear plant, and a city confronted to multiple catastrophic scenarios). The cases studies were realized by conducting three Focus Groups with different types of stakeholders (citizens, teachers, firemen, decision-makers, etc.). After presenting the results of the case studies, we discuss how stakeholders' participation can inform such type of vulnerability analysis in the context of emergency planning. We argue that participation fosters a deep understanding of actual safety governance practices which allows innovative results to emerge as well as it initiates a learning process among the participants. It contributes to questioning the relations between decision-makers, experts, and citizens. It has the potential of bypassing the positivist and quantitative rationale of safety, and thus, of redefining the vulnerability governance. As a conclusion, we question the role of such STS vulnerability approach within the actual vulnerability governance.